The effectiveness of palm-based additives in enhancing the performance of higher blend biodiesel in diesel engines - Leily Nurul Komariah; Nucke Aurelia; Syahrul Tafkiri Syayiat; Faisal Akbar Adin (Oil Palm Research and Review, 2020)
The effectiveness of palm-based additives in enhancing the performance of higher blend biodiesel in diesel engines